In silico design, synthesis and anti-HIV activity of quinoline derivatives as non-nucleoside reverse transcriptase inhibitors (NNRTIs). (June 2022) - Singh, Vishal K.; Mishra, Richa; Kumari, Priyanka; Som, Anup; Yadav, Aditya K.; Ram, Nand K.; Kumar, Pradeep; Schols, Dominique; Singh, Ramendra K.
Abstract: A series of quinoline derivatives has been designed, synthesized and screened for their anti-HIV properties. The drug-like properties of compounds were evaluated first and then molecular docking using DS v20.1.0.19295 software showed that the compounds behaved as non-nucleoside reverse transcriptase inhibitors (NNRTIs) while interacting at the allosteric site of target HIV-RT protein (PDB:3MEC). The docking results revealed that all compounds formed hydrogen bonds with Lys101, Lys103, Val179, Tyr188, Gln190, Gly190, Pro225, Phe227, and Tyr318, and showed π-interaction with Tyr188 and Tyr318. TOPKAT (Toxicity Prediction by Komputer Assisted Technology) results confirmed that the compounds were found to be less toxic than the reference drugs. Density functional theory (DFT) analysis was performed to assess the binding affinity of all compounds. Further, molecular dynamics (MD) simulations were performed on compound 6 and delavirdine with HIV-RT enzyme. Comprehensive MD analyses showed a similar pattern of conformational stability and flexibility in both the complexes suggesting alike inhibitory action. The hydrogen-bonding interactions and the binding energy of active-site residues for the compound 6 complex revealed strong inhibitory activity than the reference (delavirdine) complex. Thus, the compound 6 might act as a potential inhibitor against HIV-RT. Overall, this study revealed that compound 6 (5-hydroxy-N-(4-methyl-2-oxo-1, 2-dihydroquinolin-8-yl) thiophene-2-sulfonamide) has prudent anti-HIV activity against both HIV-1 (SI = 2.65) and HIV-2 (SI = 2.32) that can further be utilised in drug discovery against HIV virus. Graphical Abstract: ga1 Highlights: New quinoline derivatives designed and synthesized as anti-HIV agents. Molecular docking studies showed the stable ligand-protein complexes formation by all compounds. Molecular dynamics simulation illustrated strong inhibitory activity of compound 6 against HIV RT. Cytotoxicity assay against HEK293 cell lines proved low cytotoxicity of the active analogues. Anti-HIV screening of quinoline derivatives showed that compound 6 was active against both HIV-1 and HIV-2.